Age-related changes in myostatin expression in rat skeletal muscles - Tsubasa Shibaguchi; Takeshi Maeoka; Toshinori Yoshihara; Hisashi Naito; Katsumasa Goto; Toshitada Yoshioka; Takao Sugiura (Japanese Society of Physical Fitness and Sports Medicine, 2018)
Recent evidence suggests that myostatin, a negative regulator of skeletal muscle growth, may play a key role in age-related muscle loss (sarcopenia). However, there is still no unified view on the changes in myostatin protein expression in skeletal muscle with aging. Therefore, this study was to investigate the age-associated changes in the protein expression of myostatin in both slow and fast rat skeletal muscles. Slow soleus and fast plantaris (PL), extensor digitorum longus (EDL), and tibiaris anterior (TA) muscles were dissected from male Wistar strain rats at different ages (7 weeks, and 1 and 2 years). A significant loss of muscle mass and myofibrillar protein content was observed between 1 year and 2 years of age in both slow soleus and fast PL, EDL, and TA muscles. Aging also resulted in a shift of myosin heavy chain expression toward slower isoforms in both slow and three fast skeletal muscles, although this isoform shift was already noted at 1 year of age. In contrast to these age-related changes, western blot analysis showed significantly higher expression of myostatin in fast PL, EDL, and TA, not in slow soleus, muscles in the 2-year-old group compared to the 7-week-old and 1-year-old groups. These results suggest that an age-associated increase in myostatin expression in fast skeletal muscle plays a key role in the onset and/or progression of sarcopenia, characterized by selective atrophy of fast type II muscle fibers.